2019
DOI: 10.1016/j.coldregions.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Anti-icing performance and durability of suspension plasma sprayed TiO2 coatings

Abstract: Anti-icing performance and durability of suspension plasma sprayed TiO2 coatings4. Coltec (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Low differences in ice accretion in the IWT of different materials has been also reported previously by Morita et al, where the very demanding conditions decrease the behavior differences among different materials [72]. Erbil et al found an ice accretion reduction of 27 % by Teflon when compared to Cu [73]. With other metals, the reduction was even lower.…”
Section: Rime Icesupporting
confidence: 67%
“…Low differences in ice accretion in the IWT of different materials has been also reported previously by Morita et al, where the very demanding conditions decrease the behavior differences among different materials [72]. Erbil et al found an ice accretion reduction of 27 % by Teflon when compared to Cu [73]. With other metals, the reduction was even lower.…”
Section: Rime Icesupporting
confidence: 67%
“…Superhydrophobic coatings with anti-icing properties have also been demonstrated using suspension plasma spraying (SPS) of titanium dioxide [ 88 ]. Icing wind tunnel experiments showed that, compared to commercial superhydrophobic coatings, the SPS coatings exhibit substantially superior performance in icing/deicing cyclic tests.…”
Section: Fabrication Of Superhydrophobic Surfaces With Anti-icing mentioning
confidence: 99%
“…This method was referred to as the flame spray process with hybrid feedstock injection [24]. Recently, several thermal spraying methods have been used to produce icephobic coatings, such as suspension plasma spray [26], high-velocity oxygen-fuel (HVOF) spray [27][28][29] and flame spray processes [30,31]. However, some of these technologies required additional post-treatments to render the surface water repellent [26,29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several thermal spraying methods have been used to produce icephobic coatings, such as suspension plasma spray [26], high-velocity oxygen-fuel (HVOF) spray [27][28][29] and flame spray processes [30,31]. However, some of these technologies required additional post-treatments to render the surface water repellent [26,29]. Conversely, the flame spray process with hybrid feedstock injection allows one-step processing, thus representing a potential method for large scale coating production.…”
Section: Introductionmentioning
confidence: 99%